Effects of distraction using virtual reality technology on pain perception and anxiety levels in children during pulp therapy of primary molars - Puppala Niharika; N Venugopal Reddy; P Srujana; K Srikanth; V Daneswari; K Sai Geetha (Wolters Kluwer Medknow Publications, 2018)
Objective: The aim of this study was to evaluate the influence of using virtual reality (VR) eyeglasses on severity of pain and anxiety during pulp therapy in pediatric patients considering childhood anxiety-related disorders as an important confounding factor in the dental setting. Materials and Methods: A total of 40 children aged between 4 and 8 years with no previous anxiety disorder were randomly divided into two groups. The study consisted of three consecutive treatment sessions. The two groups received pulp therapy with and without VR eyeglasses in a randomized single-blind-controlled crossover fashion. Then, at the end of each session, the patients' pain severity was assessed using Wong-Baker FACES Pain Rating Scale and state anxiety was measured by Faces version of the Modified Child Dental Anxiety Scale [MCDAS]. Changes in pulse oximeter and heart rate were recorded in every 10 min. The values obtained were tabulated and subjected to statistical analysis. Results: The study shows a significant decrease in pain perception (P < 0.001) and state anxiety scores (P < 0.001) with the use of VR eyeglasses during dental treatment. Conclusion: The results of this study provide an initial encouraging for the use of VR device during dental treatment by pediatric dentists, but additional empirical research is required.